Habitual Diet Quality Was Not Associated With Self-Reported Symptoms of You010Adults With SARS-Cov-2 Infection During the First Pandemic Wave. (14th June 2022) - Ellis, Amy; Park, Han-A; Azarmanesh, Deniz; Ferguson, Christine; Bannerman, Sydney; Hayden, Mary Margaret
Abstract: Objectives: During the initial wave of the COVID-19 pandemic, older adults were identified as a vulnerable population at high risk for severe illness and mortality. However, symptoms of infection varied widely among adults younger than 50 years old. While some younger adults experienced severe illness, as many as 40% of infected persons remained asymptomatic. Considering the known influence of diet on immune function, the purpose of this cross-sectional investigation was to explore associations between diet quality prior to infection and SARS-CoV-2 symptomatology. Methods: Between August and December 2020, an online survey was completed by 158 men and women, 18–49 years old (mean 29.9 + 8.1 years), who had recovered from SARS-CoV-2 infection within the previous 4 months. Survey questions about types and severity of symptoms were assessed for content validity by physicians, nurses, and dietitians who treated patients with SARS-CoV-2. Face validity was verified by four adults who met inclusion criteria. To assess diet quality over the previous year, the Healthy Eating Index (HEI-2015) was calculated from the 2014 Block Food Frequency Questionnaire (NutritionQuest; Berkeley, CA). Results: Average HEI-2015 was 59.7 ± 9.8 (scale 0–100). HEI-2015 scores did not significantly differ between participants who did or did not report symptoms of fever, chills, cough, shortness of breath, aches, red eyes, headache, loss of taste/smell, rash, congestion, fatigue, nausea, or diarrhea. In a linear regression model adjusted for age, HEI-2015 was also not associated with a composite score of symptom severity (standardized β = −0.021, p = 0.791, R 2  = 0.011). Conclusions: Habitual diet quality prior to infection was not associated with SARS-CoV-2 symptom severity among this cohort of young adults. Although average HEI-2015 scores indicate suboptimal overall diet quality among respondents, inherent limitations of self-reported symptoms and dietary intake should be acknowledged. Funding Sources: The University of Alabama Joint Institute Pandemic Pilot Project.